Completeness of the description of manipulation and mobilisation techniques in randomized controlled trials in neck pain; A review using the TiDieR checklist. (February 2020) - Pool, Jan; Maissan, Francois; de Waele, Nanna; Wittink, Harriet; Ostelo, Raymond
Abstract: Study design: A secondary analysis of a systematic review. Background: Manipulations or mobilizations are commonly used interventions in patients with mechanical neck pain. The treatment effects have often been studied in randomized controlled trials (RCT) which are generally considered the gold standard in evaluating the treatment effects, mainly due to its high internal validity. External validity is defined as the extent to which the effects can be generalised to clinical practice. An important prerequisite for this is that interventions used in clinical trials can be replicated in clinical practice. It can be questioned if interventions utilized in randomized controlled trials can be translated into clinical practice. Objectives: The overall aim of this study is to examine whether the quality of the description of manipulation and mobilization interventions is sufficient for to replication of these interventions in clinical practice. Methods: A comprehensive literature search was performed. Two independent researchers used the Template for Intervention Description and Replication (TIDieR) which is a 12-item checklist for describing the completeness of the interventions. Results: Sixty-seven articles were included that used manipulation and/or mobilization interventions for patients with mechanical neck pain. None of the articles describe the intervention e.g. all the items on the TIDieR list. Considering item 8 (a-f) of the TIDieR checklist only one article described the used techniques completely. Conclusion: Manipulation or a mobilization interventions are poorly reported in RCTs, which jeopardize the external validity of RCTs, making it difficult for clinicians and researchers to replicate these interventions. Highlights: Manipulation or mobilization techniques are difficult to replicate. Poor reporting jeopardizes the external validity of RCTs. Due to poor reporting it is difficult to judge the effectiveness of interventions. A checklist like the TIDieR checklist should be recommended.